2004
DOI: 10.1023/b:joec.0000017985.89897.c3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anal Secretions from Phlaeothripine Thrips

Abstract: The anal secretions of 16 phlaeothripine thrips species (Thysanoptera: Phlaeothripidae) were studied, including a reinvestigation of three species previously reported. A total of 37 components were detected, including hydrocarbons, acetates, terpenes, carboxylic acids, a quinone, an aromatic compound, and a pyranone compound. The secretions of all species were composed of some of these components, with Xylaplothrips inquilinus possessing as many as 11 components. Of these components, (Z)-9-octadecene, (Z)-9-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 2 publications
1
31
0
Order By: Relevance
“…Unsaturated aliphatic hydrocarbons in anal secretions of Thysanoptera were described by Howard et al (1987) and Suzuki et al (2004), e.g. heptadecadiene in some Docessissophothripini.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Unsaturated aliphatic hydrocarbons in anal secretions of Thysanoptera were described by Howard et al (1987) and Suzuki et al (2004), e.g. heptadecadiene in some Docessissophothripini.…”
Section: Discussionmentioning
confidence: 91%
“…A heptadecadiene is also the main compound in Holothrips yuasai Karny. A nonadecadiene in Thysanoptera was detected in Eugynothrips (Loepothrips) intorquens (Karny) by Suzuki et al (2004); however, it is not structurally identified. Alkanes and alkenes in insect secretions take on various functions, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the thrips occasionally reaching high densities (>20 adults/ leaf), they may be protected from predators by defensive allomones as is known from other thrips species (Blum et al 1992;Suzuki et al 2004). These defenses are characteristically produced in thrips when disturbed and can be recognized by the raised abdomen tip that secretes a droplet of repellent liquid (Lewis 1973).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 2-methylbutanoic acid and dodecane are components of the thrips pheromone and allomons [29,30]. Western flower thrips showed a significant electro-antennographic response to-humulen [31], and (E)-β-ocimene was determined as minor component with synergetic activity in composition of aggregated pheromone of this pest [32].…”
mentioning
confidence: 99%